Prevalence and Risk Factors of Diabetic Retinopathy in Patients with type 2 Diabetes - Chaisongkram, Warangkana (Journal of Health Science of Thailand, 2017)
Diabetic retinopathy remains the most common cause of blindness in diabetes patients. This study aimed to determine prevalence and risk factors associated with diabetic retinopathy in patients with diabetes type 2 in Wichianburi Hospital, Phetchabun Province. A cross-sectional, hospital-based study was con-ducted from October 2013 to March 2014. Diabetic retinopathy screening was performed by retinal examination with indirect ophthalmoscope or non-mydriatic fundus camera. There were altogether 5,559 diabetes patients from whom fundus examination was performed in 1,526 cases. The prevalence of dia-betic retinopathy was found to be 27.6%, with 25.8% non-proliferative diabetic retinopathy and 1.8% proliferative diabetic retinopathy. The risk factors for diabetic retinopathy were age <60 (odds ratio (OR) 1.57), duration of diabetes >10 years (OR 4.131), insulin therapy (OR 5.733), hypertension (OR 1.244), on aspirin (OR 1.754), diabetic neuropathy (OR 3.114), HA1C >7% (OR 1.881), UACR >30 mg/g (OR 2.529), creatinine >2 mg/dL (OR 3.44). No evidence of association between sex, hyperlipidemia and diabetic retinopathy. The author concluded that the prevalence of diabetic retinopathy in large distinct hospital in Thailand was approximately one-fourth of diabetes patients type 2; and the risk factors were age, duration of diabetes, insulin treatment and aspirin therapy, hypertension, high HA1C level, diabetic neuropathy and nephropathy. Retinal examination of diabetes patients should be performed annually, with closed follow up in patient with one or more risk factors.